Dental aspects of purging bulimia - Manevski, Jovana; Stojšin, Ivana; Vukoje, Karolina; Janković, Ognjenka (Vojnosanitetski pregled, 2021)
Background/Aim. Bulimia is in many cases followed by frequent vomiting, which in long term can result in irreversible loss of dental tissue, most commonly manifested as dental erosion. Frequent purging, xerostomia, lack of oral hygiene and acidic environment are also suitable for caries development. The aim of the research was to determine the presence, localization and degree of dental erosion using Basic Erosive Wear Examination (BEWE) index system, as well as to determine the Decayed, Missing and Filled Teeth (DMFT) index in purging bulimic patients. Methods. The study involved 30 purging bulimic patients and 30 healthy subjects. Used methods were survey (questionnaire) and clinical examination. The clinical examination included intraoral inspection and assessment of dental status using BEWE and DMFT index. Results. On the bases of conducted research, it has been found that dental erosion are significantly more often present in purging bulimics compared to the controls (χ2 = 5.963, p
Keywords: bulimia; dental caries; oral health; risk assessment; surveys and questionnaires; tooth erosion; vomiting